Pengaruh Media Pembelajaran Terhadap Minat Belajar dan Motivasi Belajar Yang Akan Berdampak Pada Hasil Belajar Peserta Didik Kelas XI Dalam Pembelajaran Produktif Jurusan Multimedia (Studi Kasus: SMK Negeri 11 Malang) - Fadillah Eka Putri; Satrio Hadi Wijoyo; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Learning media is always used by teachers to channel productive learning material while teaching class XI in Multimedia. But problems found in learning activities related to learning interest, learning motivation and learning outcomes. The purpose of this study is to analyze the effect of learning media on learning interest and motivation to learn which will have an impact on learning outcomes. For data collection, observations, interviews, questionnaires and collection of UTS values ​​were conducted. The sample in this study were 82 students. Data is processed using linear regression analysis, t-test and f-test and coefficient of determination. From the processing of data obtained results, namely: Learning media partially affects the interest in learning with the direction of positive influence, as evidenced from 9.420> t table 1.993 with a significance level of 5%; learning media partially influence learning motivation with the direction of positive influence, as evidenced from t count 9.012> t table 1.993 with a significance level of 5%; interest in learning partially does not affect learning outcomes with the direction of negative influence, as evidenced from t-count -0.656 <1.993 t table with a significance level of 5%; Partial learning motivation does not affect learning outcomes with a positive direction, as evidenced by 0.127 <1.993 t table with a significance level of 5%; and the interest in learning and learning motivation simultaneously did not affect the learning outcomes, as evidenced by the calculation of 0.775 <table 3.09 with a significance level of 5%.